Tinjauan Yuridis Terhadap Tindak Pidana Penggelapan Oleh Karyawan Melalui Transaksi Fiktif Dana Operasional Perusahaan (Studi Kasus Putusan Nomor 21/Pid.B/2025/PN Ptk) - Simanungkalit, Dohma Pungu Nathanael; Karli, Karli (HUMANIORUM, 2025)
This study aims to examine the legal classification of the criminal offense of embezzlement committed in an official capacity and carried out continuously, as well as the application of criminal law in judicial practice, using Case Decision Number 21/Pid.B/2025/PN Ptk as a reference point. In this case, the defendant, who served as a financial staff member at CV Setia Andhika Sejahtera, was found guilty beyond reasonable doubt of systematically embezzling company operational funds through fabricated transactions from May to August 2023. The defendant submitted false financial requests and diverted the approved funds into a personal bank account without the company's knowledge, resulting in a financial loss of IDR 476,600,000.00. This research adopts a normative legal approach, grounded in statutory and conceptual analysis, and utilizes primary, secondary, and tertiary legal materials. The court concluded that the defendant’s actions fulfilled all elements of Article 374 of the Indonesian Criminal Code in conjunction with Article 64 paragraph (1), which governs repeated embezzlement by individuals in positions of trust. Consequently, the panel of judges sentenced the defendant to two years and three months of imprisonment. The legal reasoning and outcome in this case reflect the principles of legal certainty and justice for both the victim and the perpetrator.